The influence of school furniture on students' performance and physical responses: results of a systematic review. Issue 1 (2nd January 2017) - Castellucci, H. I.; Arezes, P. M.; Molenbroek, J. F. M.; de Bruin, R.; Viviani, C.
Abstract: The purpose of this study was to determine, using a systematic review, whether the design and/or dimensions of school furniture affect the students' physical responses and/or their performance. Of the review studies, 64% presented positive results, i.e. proven effects; 24% presented negative effects or no change/effect; and the remaining 12% showed an unclear effect. The compatibility between school furniture dimensions and students' anthropometric characteristics was identified as a key factor for improving some students' physical responses. Design characteristics such as high furniture, sit-stand furniture, and tilt tables and seats also present positive effects. Finally, we concluded that further research should be conducted exploring various aspects of those variables, particularly focusing on more objective measures complemented by controlled and prospective design. Practitioner Summary: A systematic review of the literature presents a clearly positive effect of school furniture dimensions on students' performance and physical responses. Similar results appeared when school furniture design was tested. However, studying the effects of design and dimensions together produced an unclear positive effect.